Physics Education Technology (PhET) as Confirmatory Tools in Learning Physics - Pranata, Ogi Danika (Universitas PGRI Sumatera Barat, 2023)
Teaching physics are always challenging tasks. Teachers need to be responsive to their students’ needs. The best tool to utilized is Physics Education Technology (PhET). PhET provides features that support learning and teaching physics, including testing. These feature can be expanded as confirmatory tools for students. To explore and compare the tests result between two groups of students, the quantitative experimental methods was applied. The first group took the test using graph paper and with confirmatory tools. The other group took the test without any tools. The students’ answer were graded using vector assessment rubric. The collected data were analyzed descriptively and using an independent sample t-test. The results showed that the group of students who use PhET simulation obtained significanly different results (ρ=0.000), with average score of 80.43, which was higher than other group (62.35). The effect size was approximately 1.07, which is much larger than typical sized effect.